X-ray photoelectron study on gold/nanocrystalline cellulose-graphene oxide thin film as surface plasmon resonance active layer for metal ion detection - Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Yap, Wing Fen; Abdullah, Jaafar; Hashim, Hazwani Suhaila; Muhamad Fauzi, Nurul ‘Illya; Chanlek, Narong; Mahdi, Mohd Adzir (Elsevier, 2020)
X-ray photoelectron spectroscopy (XPS) is a spectroscopic technique that is surface-sensitive that can be used to analyze the chemical and elemental state of a sample on the surface. In this research, XPS was used to study the chemical interaction of gold/nanocrystalline cellulose-graphene oxide (gold/NCC-GO) thin film. The thin film was prepared by deposition of NCC-GO on a gold thin film using spin coating method to obtain a homogeneous gold/NCC-GO thin film before characterized by XPS. From the XPS results, it is confirmed that carbon, oxygen, nitrogen, and sulfur elements exist on the gold/NCC-GO thin film surface. Further deconvolution has also been carried out by Voigt curve fitting program in order to determine the sub-peak component of each elements. Besides that, the gold/NCC-GO thin film has potential to be used in sensing metal ion application. The interaction of metal ions with the gold/NCC-GO thin film was optically proven using surface plasmon resonance optical sensor before the thin film was characterized again by XPS to confirm the chemical interactions involved. It is believed that the existence negative charge functional groups, i.e., COO− and SO3− on the gold/NCC-GO thin film surface played an important role during the interaction.